2017
DOI: 10.1097/gox.0000000000001294
|View full text |Cite
|
Sign up to set email alerts
|

Local Application of Statins Significantly Reduced Hypertrophic Scarring in a Rabbit Ear Model

Abstract: Background:We previously showed that intradermal injection of statins is a successful treatment for hypertrophic scarring. Topical application has many advantages over intradermal injection. In this study, we demonstrate the efficacy of topical statin treatment in reducing scar in our validated rabbit ear scar model.Methods:Twenty New Zealand White rabbits were divided into 2 study groups, with 6 rabbits receiving 10 μm pravastatin intradermally at postoperative days 15, 18, and 21, and 14 rabbits receiving 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…The thickness of stratum corneum and the density of hair follicles in the skin of the inner rabbit ear are more similar to that of human skin compared to rodent skin . Furthermore, we have extensive experience in establishing models in the rabbit ear including wound repair, hypertrophic scar, and atopic dermatitis models . Here, we demonstrated that, following repeated challenges of IMQ, dermatosis that parallels human psoriasis emerged in rabbit ear skin characterized by excessive keratinocyte proliferation (acanthosis), insufficient keratinocyte differentiation (parakeratosis) and infiltration of inflammatory cells, including neutrophils, macrophages, T cells and mast cells.…”
Section: Discussionmentioning
confidence: 81%
“…The thickness of stratum corneum and the density of hair follicles in the skin of the inner rabbit ear are more similar to that of human skin compared to rodent skin . Furthermore, we have extensive experience in establishing models in the rabbit ear including wound repair, hypertrophic scar, and atopic dermatitis models . Here, we demonstrated that, following repeated challenges of IMQ, dermatosis that parallels human psoriasis emerged in rabbit ear skin characterized by excessive keratinocyte proliferation (acanthosis), insufficient keratinocyte differentiation (parakeratosis) and infiltration of inflammatory cells, including neutrophils, macrophages, T cells and mast cells.…”
Section: Discussionmentioning
confidence: 81%
“…Thirteen New Zealand white rabbits at 3‐6 months age were purchased from Covance Research Products, Inc (Cumberland, VA), and acclimatized in the temperature‐controlled animal facility with a 12‐hour light/dark cycle for at least 1 week. The rabbit ear HTS model was created as previously described 12 . Briefly, under anesthesia with ketamine and xylazine, six paired, full‐thickness, 7‐mm diameter circular excisional wounds were created on the depilated ventral side of rabbit ears with biopsy punches and covered with Tegaderm (3M Health Care, St. Paul, Minnesota).…”
Section: Methodsmentioning
confidence: 99%
“…The HTS tissue was harvested on POD 28 for analysis of scar elevation index and gene expression. Topical application of statins to the skin has been demonstrated to cause symptoms of cutaneous scaling, 12 of which the severity and reversibility were observed after withdrawal of statin treatment on POD 25, until POD 42. All the animal procedures in this study were approved by Northwestern University Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low doses of simvastatin, lovastatin, and pravastatin were associated with a significant reduction in SEI when compared to controls. A dose responsive effect has been observed in scar reduction at low, medium, or high doses of simvastatin for topical application 30,31 . High doses of simvastatin are associated with a significant reduction in the expression of the mRNA of CTGF 28,30 .…”
Section: Discussionmentioning
confidence: 99%